A method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology

Through the detection method based on nano-indentation technology, combined with the Suresh model to calculate the residual thermal stress of the porcelain casing, the problem of the lack of effective crack state detection methods for high-voltage electrical porcelain casing is solved, and scientific support for the analysis and prevention of porcelain casing accidents is achieved. .

CN119164529BActive Publication Date: 2025-02-25NEI MENG GU CHAO GAO YA GONG DIAN JU
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411659849.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The high-voltage porcelain casing lacks effective mechanical strength (especially crack) state detection methods during operation, resulting in insufficient ability to prevent explosion accidents.

Method used

Using a detection method based on nano-indentation technology, a slight load is applied to the surface of the porcelain casing through a nano-indentation meter to measure the formation and deformation of the indentation, and the residual thermal stress of the porcelain casing is calculated in combination with the Suresh model.

Benefits of technology

This method can accurately evaluate the residual thermal stress state of the porcelain casing on a microscopic scale, provide scientific basis for accident analysis and prevention, and improve the safety and reliability of the power system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164529B_ABST
    Figure CN119164529B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of thermal stress detection technology, and in particular refers to a method for detecting thermal stress of high-voltage electric porcelain bushings based on nanoindentation technology, the steps of which include performing a performance test on a nanoindentation tester to determine that its error is within a normal error range; cutting the high-voltage electric porcelain bushings that have been cracked and damaged into a plurality of samples to be screened suitable for nanoindentation testing, and screening test samples suitable for nanoindentation testing; performing an indentation experiment, and recording the load-displacement curve of the indenter; analyzing the load-displacement curve; substituting the Suresh model formula to calculate the residual thermal stress of the porcelain bushing; analyzing the stress distribution inside the porcelain bushing by comparing the residual thermal stress in different regions; and evaluating the damage mode of the porcelain bushing. The present invention utilizes nanoindentation technology and the Suresh model to accurately evaluate the residual thermal stress state of the porcelain bushing at a microscopic scale, and the method is simple to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal stress detection, and in particular refers to a method for detecting thermal stress of a high-voltage porcelain bushing based on nano-indentation technology. Background Art

[0002] In the field of bioenergy, especially in the process of power generation and transmission of biomass energy, the safe operation of high-voltage electrical equipment is crucial to the stability and efficiency of the entire system. As a key insulating component in power equipment, the reliability of high-voltage porcelain bushings is directly related to the safe and stable operation of the system. However, there are two major problems with porcelain bushings in practical applications: first, the porcelain bushings themselves have high brittleness, low fracture toughness, small damage tolerance, and are extremely sensitive to cracks; second, the porcelain bushings lack effective means of detecting the mechanical strength (especially cracks) status during operation, resulting in insufficient ability to prevent explosion accidents.

[0003] Residual thermal stress is the stress remaining inside the object due to uneven temperature changes, plastic deformation or phase change during the manufacturing process. This stress exists in a balanced state inside the object when there is no external factor, and has a very important influence on the shape, size and performance of the component. In high-voltage porcelain bushings, the presence of residual thermal stress can easily lead to sudden damage, and the consequences are often very serious, especially when it exists on load-bearing parts and rotating parts, which may cause major accidents.

[0004] During the operation of the porcelain bushing, thermal stress will be generated due to the temperature difference between the inside and outside. This thermal stress forms a mutually balanced tensile and compressive stress between the surface and the inside of the porcelain bushing. At room temperature, the surface is usually subject to compressive stress, while the inside is subject to tensile stress, which is also called thermal stress. In addition, the stress generated during the phase change process, such as eutectic crystallization and eutectoid transformation in cast iron, will also lead to the generation of residual thermal stress.

[0005] Traditional residual thermal stress detection methods include mechanical measurement and non-destructive measurement. Mechanical measurement methods, such as the blind hole method, release local residual stress by drilling holes on the workpiece, thereby calculating the magnitude of residual stress. Non-destructive measurement methods include X-ray diffraction, magnetic and ultrasonic methods, which indirectly calculate residual stress by measuring the changes in physical constants inside the material. However, these methods have certain limitations when detecting porcelain bushings, such as high requirements for surface conditions or inability to accurately measure internal stress distribution. Nanoindentation technology, as an emerging material mechanical property testing method, has been widely used in the detection of metals, alloys, semiconductors, glass, minerals and organic materials due to its advantages such as high precision and high resolution. The nanoindenter uses a diamond probe to apply a tiny load on the surface of the material, give the test material an indentation, measure the formation and deformation of the indentation, and infer the residual thermal stress state inside the material by analyzing the changes in the load-displacement curve. This method can reveal the mechanical response of the material due to residual thermal stress during the force process, thereby providing important data for evaluating the safety and reliability of the material.

[0006] Therefore, developing a residual thermal stress detection method for high-voltage porcelain bushings based on nanoindentation technology is of great significance for analyzing the residual thermal stress of bushings that have been damaged by explosion. Summary of the invention

[0007] The present invention aims to provide a method for detecting thermal stress of high-voltage porcelain bushings based on nanoindentation technology, specifically for analyzing residual thermal stress of bushings that have been damaged by explosion. Through this method, the residual thermal stress state of the damaged bushing can be evaluated, providing a scientific basis for accident analysis and prevention.

[0008] The technical solution adopted by the present invention to solve the technical problem is: a method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology, comprising the following steps:

[0009] Step 1, perform a performance test on the nanoindentation tester to determine that its error is within a normal error range;

[0010] Step 2: When the error of the nanoindentation tester is within the normal error range, the damaged high-voltage porcelain bushing is cut into a plurality of samples to be screened suitable for nanoindentation testing, and the sample surface data of each sample is obtained after the samples to be screened are polished, and the test samples suitable for nanoindentation testing are screened based on the sample surface data, wherein the sample surface data includes surface roughness, surface glossiness, number of surface cracks, and number of surface stains;

[0011] Step 3, using a nanoindenter within a normal error range to perform an indentation experiment on the test sample, and recording the load-displacement curve of the indenter;

[0012] Step 4: Analyze the load-displacement curve and calculate the contact area A and the maximum load P. max The contact area A 0 ;

[0013] Step 5: Combine the contact areas A and A determined in the experiment 0 , and the hardness H of the material are substituted into the Suresh model formula to calculate the residual thermal stress of the porcelain bushing;

[0014] Step 6: Analyze the stress distribution inside the porcelain bushing by comparing the residual thermal stress in different areas;

[0015] Step 7: Evaluate the damage mode of the porcelain bushing based on the distribution and magnitude of the residual thermal stress.

[0016] Preferably, in step 1, a performance test is performed on the nanoindentation tester to determine that its error is within a normal error range, including the following steps:

[0017] Use a nanoindentation tester to perform an indentation experiment on a standard material to obtain standard material test data, which includes test indentation recovery rate, test unloading curve slope, test depth drift rate, and test elastic modulus;

[0018] Obtain actual data of standard materials, including actual indentation recovery rate, actual unloading curve slope, actual depth drift rate, and actual elastic modulus;

[0019] The standard material test data and the standard material actual data are processed to obtain the standard material test deviation data, which includes the indentation recovery rate deviation, the unloading curve slope deviation, the depth drift rate deviation, and the elastic modulus deviation;

[0020] Based on the standard material test deviation data and the material test deviation allowable data stored in the database, the test deviation matching value is obtained. The material test deviation allowable data includes the indentation recovery rate allowable deviation, the unloading curve slope allowable deviation, the depth drift rate allowable deviation and the elastic modulus allowable deviation;

[0021] The test deviation matching value is compared with the test deviation matching value threshold stored in the database. If the test deviation matching value is less than the test deviation matching value threshold, the error of the nanoindentation tester is within the normal error range.

[0022] If the test deviation matching value is not less than the test deviation matching value threshold, the error of the nanoindentation tester is outside the normal error range, and the standard material test deviation data is compared with the standard material test deviation matching data stored in the database to determine the closest standard material test deviation matching data;

[0023] Based on the closest standard material test deviation matching data, the nanoindentation tester failure cause corresponding to the closest standard material test deviation matching data stored in the database is obtained.

[0024] Preferably, the determining of the closest standard material test deviation matching data comprises the following steps:

[0025] Comprehensively analyze the standard material test deviation data and the standard material test deviation matching data stored in the database to obtain the test comparison value. The standard material test deviation matching data includes the indentation recovery rate matching deviation, the unloading curve slope matching deviation, the depth drift rate matching deviation, and the elastic modulus matching deviation;

[0026] The standard material test deviation matching data stored in the database corresponding to the largest test comparison value is the closest standard material test deviation matching data.

[0027] Preferably, in step 2, the damaged high-voltage porcelain bushing is cut into samples with a diameter less than Φ50 mm and a height less than 10 mm, and the sample surface is ground and polished to ensure that the roughness of the loading surface reaches the nanometer level and is less than 1 / 5 of the average indentation depth; the upper and lower end surfaces of the sample are parallel to each other to ensure uniform distribution of the load during the indentation process.

[0028] Preferably, in step 2, screening test samples suitable for nanoindentation testing based on sample surface data comprises the following steps:

[0029] Determine whether the number of surface cracks or surface stains is not zero. If any of them is not zero, the surface treatment is unqualified and the sample is marked as unsuitable for nanoindentation testing.

[0030] If both are zero, the sample surface definition data is obtained, and the sample surface definition data includes surface definition roughness and surface definition glossiness;

[0031] Acquire the sample surface allowable deviation data, the sample surface allowable deviation data includes the roughness allowable deviation value and the gloss allowable deviation value;

[0032] Comprehensively analyze the sample surface data, sample surface definition data and sample surface allowable deviation data to obtain the surface treatment comparison value;

[0033] The surface treatment comparison value is compared with the surface treatment comparison threshold stored in the database. If the surface treatment comparison value is less than or equal to the surface treatment comparison threshold, the surface treatment of the sample to be tested is qualified and is marked as a test sample capable of nanoindentation testing.

[0034] If the surface treatment comparison value is greater than the surface treatment comparison threshold, the size of the sample to be tested is unqualified and cannot be subjected to nanoindentation testing. In this case, the sample is replaced and polished again.

[0035] Preferably, the obtaining of sample surface allowable deviation data comprises the following steps:

[0036] Acquire an allowable deviation data matching set stored in a database, the allowable deviation data matching set including allowable deviation matching data, and the allowable deviation matching data including an environment comparison brightness and an indoor dust content comparison value;

[0037] Obtaining the detection environment data when collecting the sample surface data of the sample to be screened, the detection environment data includes the environment brightness and indoor dust content;

[0038] Compare the detection environment data with the allowable deviation matching data to obtain the comparison coefficient;

[0039] The allowable deviation matching data corresponding to the largest comparison coefficient corresponds to the sample surface allowable deviation data stored in the database, which is the sample surface allowable deviation data corresponding to the detection environment data.

[0040] Preferably, in step 3, when performing nanoindentation testing on the sample, the indenter randomly selects an area on the loading surface of the sample and performs multiple indentations using a dot matrix method to form an indentation point array, and collects a load-displacement curve of the indenter during each indentation;

[0041] The indenter is a diamond Berkovich indenter;

[0042] The row and column spacing of the indentation point array is 300 μm, and the indentation load of the indenter is 10 mN;

[0043] Determine the contact point in the load-displacement curve, that is, the point where the load suddenly increases, marking the first time the indenter contacts the sample surface; in step 3, extract the contact area A and the maximum load P in the elastic region of the curve, that is, the part of the curve that is linear. max The contact area A 0 ;

[0044] In step 4, calculate the contact area A. For the Berkovich indenter, use the formula to calculate;

[0045] Where: h is the penetration depth of the indenter, S is the contact stiffness, is the elastic modulus of the indenter, P is the load applied by the indenter;

[0046] In step 5, the Suresh model calculates the residual thermal stress The formula is:

[0047] .

[0048] Preferably, in step 6, analyzing the stress distribution inside the porcelain bushing includes the following steps:

[0049] Calculate the mean value and standard deviation of residual thermal stress of all pressing points;

[0050] The residual thermal stress value is normalized, and the stress concentration area is determined based on the normalized residual thermal stress value. The stress concentration area includes a high stress concentration area, a medium stress concentration area, and a low stress concentration area:

[0051] The area where the normalized residual thermal stress value is greater than the first threshold is defined as a high stress concentration area;

[0052] A region where the normalized residual thermal stress value is not greater than the first threshold value but greater than the second threshold value is defined as a medium stress concentration region;

[0053] A region where the normalized residual thermal stress value is not greater than the second threshold but greater than the third threshold is defined as a low stress concentration region.

[0054] Preferably, in step 7, the damage mode of the porcelain bushing is evaluated according to the distribution and magnitude of the residual thermal stress, which specifically includes the following steps:

[0055] Obtaining stress area proportion data, the stress area proportion data including high stress area proportion, medium stress area proportion and low stress area proportion;

[0056] Obtaining standard deviation data of residual thermal stress in stress regions, wherein the standard deviation data of residual thermal stress in stress regions include standard deviation of residual thermal stress in high stress concentration regions, standard deviation of residual thermal stress in medium stress concentration regions, and standard deviation of residual thermal stress in low stress concentration regions;

[0057] A damage mode stress condition set stored in a database is obtained, the damage mode stress condition set includes a number of damage mode stress condition data, the damage mode stress condition data includes stress area proportion parameter data, high stress concentration area residual thermal stress parameter standard deviation, medium stress concentration area residual thermal stress parameter standard deviation and low stress concentration area residual thermal stress parameter standard deviation, stress area proportion parameter data includes high stress area proportion parameter value, medium stress area proportion parameter value and low stress area proportion parameter value;

[0058] The stress area proportion data and the residual thermal stress standard deviation data of the stress area are combined and recorded as the actual situation data of the stress area;

[0059] Compare the actual situation data of the stress area with the stress situation data of the damage mode one by one to obtain the stress situation comparison value;

[0060] The damage mode corresponding to the minimum stress comparison value stored in the database is recorded as the damage mode of the high-voltage porcelain bushing that has been damaged by explosion.

[0061] Preferably, the calculation formula of the stress condition comparison value is as follows:

[0062] ;

[0063] Where: is the stress comparison value obtained by comparing the actual data of the stress area with the stress data of the ath damage mode. is the stress area comparison coefficient of the stress condition data of the ath damage mode, is the stress area standard deviation comparison coefficient of the stress condition data of the ath damage mode, Stored in the database The weight factor of Stored in the database The weight factor of , a is the number of the damage mode stress condition data;

[0064] The calculation formula of stress area comparison coefficient is as follows:

[0065] ;

[0066] Where: is the proportion of high stress area, is the proportion of the medium stress area, is the proportion of low stress area, is the parameter value of the proportion of high stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the medium stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the low stress area in the stress condition data of the ath damage mode;

[0067] The calculation formula of stress area standard deviation comparison coefficient is as follows:

[0068] ;

[0069] Where: is the standard deviation of residual thermal stress in high stress concentration area, is the standard deviation of residual thermal stress in the stress concentration area, is the standard deviation of residual thermal stress in the low stress concentration area, is the standard deviation of residual thermal stress parameters in the high stress concentration area of ​​the stress condition data of the ath damage mode, is the standard deviation of residual thermal stress parameters in the stress concentration area of ​​the a-th damage mode stress condition data, is the standard deviation of the residual thermal stress parameter in the low stress concentration area of ​​the stress condition data of the ath damage mode.

[0070] The present invention has the following beneficial effects:

[0071] The present invention utilizes nanoindentation technology and the Suresh model to accurately evaluate the residual thermal stress state of the porcelain bushing at a microscopic scale. The method is simple to operate, has low requirements for sample preparation, and is applicable to damaged porcelain bushing samples of various shapes and sizes. It provides an effective method for residual thermal stress analysis of exploded and damaged high-voltage porcelain bushings, provides a scientific basis for accident analysis and prevention of high-voltage porcelain bushings, and helps to improve the safety and reliability of power systems involved in bioenergy. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0073] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0074] A method for detecting thermal stress of high-voltage porcelain bushings based on nanoindentation technology, such as Figure 1 As shown, the following steps are included:

[0075] Step 1: Perform a performance test on the nanoindentation tester to determine that its error is within the normal error range.

[0076] Use a nanoindentation tester to perform an indentation experiment on a standard material to obtain standard material test data, which includes test indentation recovery rate, test unloading curve slope, test depth drift rate, and test elastic modulus; obtain actual data of the standard material, which includes actual indentation recovery rate, actual unloading curve slope, actual depth drift rate, and actual elastic modulus; process the standard material test data and the actual data of the standard material to obtain standard material test deviation data, which includes indentation recovery rate deviation, unloading curve slope deviation, depth drift rate deviation, and elastic modulus deviation; analyze the standard material test deviation data and the material test deviation permission data stored in the database to obtain the test deviation matching value.

[0077] The test deviation matching value is obtained as follows:

[0078] ;

[0079] Where Bp is the test deviation matching value, is the indentation recovery rate deviation, is the unloading curve slope deviation, is the depth drift rate deviation, is the elastic modulus deviation, is the allowable deviation of the indentation recovery rate, is the allowable deviation of the slope of the unloading curve, is the depth drift rate allowable deviation, is the allowable deviation of elastic modulus, Stored in the database and The weighting factor of the ratio, Stored in the database and The weighting factor of the ratio, Stored in the database and The weighting factor of the ratio, Stored in the database and Weighting factor for the ratio.

[0080] The allowable data for material test deviation include the allowable deviation of indentation recovery rate, the allowable deviation of unloading curve slope, the allowable deviation of depth drift rate and the allowable deviation of elastic modulus; the test deviation matching value is compared with the test deviation matching value threshold stored in the database. If the test deviation matching value is less than the test deviation matching value threshold, the error of the nanoindentation tester is within the normal error range; if the test deviation matching value is not less than the test deviation matching value threshold, the error of the nanoindentation tester is outside the normal error range.

[0081] The test indentation recovery rate refers to the ratio of the amount of recovery due to elastic deformation inside the material to the irreversible deformation generated during the unloading process, which reflects the elastic and plastic behavior of the material. By measuring the change in indentation depth during the unloading period, the ratio of the recovery depth of the elastic part to the total indentation depth can be calculated; the slope of the test unloading curve represents the rate of change of the relationship between indentation depth and load during the unloading process, which is related to the hardness and stiffness of the material. The slope of the curve is calculated by plotting the relationship between depth (y-axis) and load (x-axis) during the unloading process; the test depth drift rate refers to the rate of change of the indentation depth of the material over time after the load is applied. It reflects the stability of the material after bearing. After the load is applied and unloading, the change in indentation depth is recorded over time to calculate the rate of change of depth; the test elastic modulus is a measure of the material's ability to resist deformation, indicating the stiffness of the material under load, and is a key indicator of the material's ability to withstand cyclic loads. The elastic modulus is calculated through the indentation loading and unloading curves combined with Poisson's ratio and other material properties.

[0082] The indentation recovery rate deviation refers to the absolute value of the difference between the tested indentation recovery rate and the actual indentation recovery rate. The unloading curve slope deviation refers to the absolute value of the difference between the tested unloading curve slope and the actual unloading curve slope. The depth drift rate deviation refers to the absolute value of the difference between the tested depth drift rate and the actual depth drift rate. The elastic modulus deviation refers to the absolute value of the difference between the tested elastic modulus and the actual elastic modulus.

[0083] By conducting standard material tests on the nanoindentation tester, we can understand whether the error of the current nanoindentation tester is within the normal error range, so as to determine whether it is currently in a usable state and whether calibration is required to ensure the accuracy and availability of data obtained during subsequent use. By using the nanoindentation tester to test standard samples, we can clearly determine whether the nanoindentation tester is within the normal working range, which can not only help to promptly discover and correct potential problems of the nanoindentation tester, but also provide protection for the safety of subsequent research and development and application of nanoindentation testers, and make more accurate and scientific decisions.

[0084] This formula can simultaneously consider multiple types of deviations (including indentation recovery rate, unloading curve slope, depth drift rate and elastic modulus) and their corresponding allowable deviations, which can comprehensively reflect the measurement performance of the equipment and quantify the deviations into digital form, making the results more scientific and reliable, reducing the risk of misjudgment, and helping to promptly discover problems with the nanoindentation tester. Accurate parameter measurement can help evaluate the performance of materials under different conditions, improve the calibration and setting of test instruments, and improve the accuracy and repeatability of tests.

[0085] The above setting , , , It is obtained from the database and historical measurements are established based on historical data. and ratio, and ratio, and ratio, and Ratio and test deviation matching value, establish and ratio, and ratio, and ratio, and The mapping set of ratios and their corresponding weight factors is used to obtain the current , , , .

[0086] In the following , They are also obtained through a mapping set of historical data and weight factors established in the database, that is, the corresponding weight factors are obtained according to the current data.

[0087] The standard material test deviation data is compared with the standard material test deviation matching data stored in the database to determine the closest standard material test deviation matching data; based on the closest standard material test deviation matching data, the nanoindentation tester failure cause corresponding to the closest standard material test deviation matching data is obtained from the database.

[0088] Comprehensively analyze the standard material test deviation data and the standard material test deviation matching data stored in the database to obtain the test comparison value. The standard material test deviation matching data includes the indentation recovery rate matching deviation, the unloading curve slope matching deviation, the depth drift rate matching deviation, and the elastic modulus matching deviation. The standard material test deviation matching data stored in the database corresponding to the largest test comparison value is the closest standard material test deviation matching data.

[0089] The test comparison value is obtained as follows:

[0090] ;

[0091] Where Cb is the test comparison value, is the indentation recovery rate deviation, is the unloading curve slope deviation, is the depth drift rate deviation, is the elastic modulus deviation, is the indentation recovery rate matching deviation, is the unloading curve slope matching deviation, is the depth drift rate matching deviation, is the elastic modulus matching deviation.

[0092] The above-mentioned test comparison value is calculated to quantify the difference between the standard material test deviation and the relevant deviation in the database. The matching data corresponding to the maximum test comparison value finally obtained is considered to be the closest standard material deviation data. The cause of the failure behind it is combined with the current test data, which can clearly point out the possible problems of the nanoindentation tester. The quantitative output can be directly used to evaluate the status of the nanoindentation tester and promote rapid response and effective management.

[0093] Step 2: When the error of the nanoindentation tester is within the normal error range, the cracked and damaged high-voltage porcelain bushing is cut into multiple samples to be screened that are suitable for nanoindentation testing, and the sample surface data of each sample is obtained after polishing the samples to be screened. Based on the sample surface data, the test samples suitable for nanoindentation testing are screened, and the sample surface data includes surface roughness, surface glossiness, number of surface cracks, and number of surface stains.

[0094] In step 2, the damaged high-voltage porcelain bushing is cut into samples with a diameter less than Φ50mm and a height less than 10mm, and the sample surface is ground and polished to ensure that the roughness of the loading surface reaches the nanometer level and is less than 1 / 5 of the average indentation depth; the upper and lower end surfaces of the sample are parallel to each other to ensure uniform distribution of the load during the indentation process.

[0095] The diameter of the porcelain bushing sample is tested by testing equipment (including vernier calipers, digital readout measuring instruments, projectors or optical measuring instruments, etc.) to be less than Φ50mm, the height of the porcelain bushing sample is tested to be less than 10mm, the surface of the porcelain bushing sample is ground and polished, and the roughness of the loading surface is polished to the nanometer level (the roughness should be less than 1 / 5 of the average indentation depth); the sample surface needs to be thoroughly cleaned with appropriate solvents or cleaning fluids (including deionized water, ethanol, acetone, isopropanol, detergents, etc.) to ensure that no foreign substances interfere with the results during the test; the upper and lower end faces of the porcelain bushing sample are parallel to each other to ensure uniform distribution of the load during the indentation process.

[0096] Determine whether the number of surface cracks and the number of surface stains is not zero. If any of them is not zero, the surface treatment is unqualified and the sample is marked as not suitable for nanoindentation testing. If both are zero, obtain the sample surface definition data, which includes the surface definition roughness and the surface definition glossiness. Obtain the sample surface allowable deviation data, which includes the roughness allowable deviation value and the gloss allowable deviation value. Comprehensively analyze the sample surface data, the sample surface definition data and the sample surface allowable deviation data to obtain the surface treatment comparison value. Compare the surface treatment comparison value with the surface treatment comparison threshold stored in the database. If the surface treatment comparison value is less than or equal to the surface treatment comparison threshold, the surface treatment of the sample to be tested is qualified and is marked as a test sample that can be tested by nanoindentation testing. If the surface treatment comparison value is greater than the surface treatment comparison threshold, the size of the sample to be tested is unqualified and cannot be tested by nanoindentation testing, so it is replaced and polished again.

[0097] The surface treatment comparison value is obtained as follows:

[0098] ;

[0099] Where Bm is the surface treatment comparison value, is the surface roughness, is the surface gloss, Define the roughness for the surface, Defines the glossiness of the surface, is the allowable deviation value of roughness, It is the allowable deviation value of glossiness.

[0100] Surface roughness refers to the degree of change in the microstructure of the sample surface, usually expressed as Ra (arithmetic mean roughness) or Rz (ten-point height), which reflects the smoothness of the sample surface and is obtained through the detection of an optical roughness meter. There is another type of contact roughness tester. If a contact tester is used, the pre-set sample surface allowable deviation data is directly obtained from the database, and there is no need to consider the detection environment. The detection environment is only considered when using an optical roughness meter; surface gloss refers to the ability of the material surface to reflect light, usually quantitatively measured by a gloss meter, reflecting the smoothness and finish of the surface. Using a gloss meter, the gloss value is calculated by measuring the intensity of the reflected light on the surface. High gloss usually corresponds to a smaller surface roughness, which helps to reduce light scattering and errors in the experiment. In nanoindentation testing, uniform gloss helps to stabilize measurement results.

[0101] The number of surface cracks refers to the total number of cracks visible on the surface of the sample. Cracks may affect the mechanical properties of the material and are obtained through visual inspection, microscopic inspection (optical microscope or scanning electron microscope) or image analysis technology. Cracks will seriously affect the strength and hardness of the material. Identifying the number of cracks helps to judge the integrity and adaptability of the sample before nanoindentation testing; the number of surface stains refers to the number of contaminants or irregular objects on the surface, which also need to be inspected and counted visually or under a microscope. Stains not only affect the physical properties of the sample, but also affect the contact conditions during the indentation test, increasing noise or errors.

[0102] By evaluating the number of surface cracks and stains on the samples, the samples are preliminarily screened to determine whether they are qualified. If the number of surface cracks and the number of surface stains are greater than zero, it means that the surface state of the sample is unqualified and cannot be used for subsequent nanoindentation tester detection, thereby preventing test errors and equipment damage caused by surface problems. If the sample has passed the preliminary screening, then the surface definition data and allowable deviation data of the sample are obtained, and the surface treatment comparison value is analyzed to obtain the surface treatment comparison value. By comparing the surface treatment comparison value with the surface treatment comparison threshold, the final judgment result is obtained to confirm whether the sample can be subjected to nanoindentation testing. Quality control can be effectively performed to ensure that nanoindentation testing is only performed on qualified samples, and potential defective samples can be excluded in a timely manner, thereby ensuring the strictness of the entire testing process, avoiding the entry of unqualified samples, and improving the reliability of the test.

[0103] Obtain an allowable deviation data matching set stored in a database, the allowable deviation data matching set includes allowable deviation matching data, and the allowable deviation matching data includes environmental comparison brightness and indoor dust content comparison values; obtain the detection environment data when collecting sample surface data of the sample to be screened, the detection environment data includes environmental brightness and indoor dust content; compare the detection environment data with the allowable deviation matching data to obtain a comparison coefficient; the allowable deviation matching data corresponding to the largest comparison coefficient corresponds to the sample surface allowable deviation data stored in the database, which is the sample surface allowable deviation data corresponding to the detection environment data.

[0104] The comparison coefficient is obtained as follows:

[0105] ;

[0106] Where Bd is the comparison coefficient, is the ambient brightness, is the indoor dust content, is the ambient comparison brightness, It is the comparison value of indoor dust content.

[0107] Ensuring a high degree of consistency between the test environment and the sample surface data enhances the effectiveness and systematicness of the nanoindentation test. By acquiring and analyzing the test environment data, we can better understand the impact of external factors on the test results, thereby ensuring the controllability of the test conditions. For example, the ambient brightness may affect the observation and optical properties of the sample surface, and the indoor dust content may affect the accuracy of the indentation test. Combining these environmental factors with the allowable deviation data in the database can obtain the best sample state in a changing environment and reduce the test errors caused by environmental factors.

[0108] Ambient brightness refers to the intensity of the light source in the test environment, while indoor dust content refers to the amount of dust per cubic meter in the test environment. These data are usually obtained in real time through sensors or detection instruments during the sample collection process.

[0109] Step 3: Use a nanoindenter within a normal error range to perform an indentation experiment on the test sample and record the load-displacement curve of the indenter.

[0110] Step 4: Analyze the load-displacement curve and calculate the contact area A and the maximum load P. max The contact area A 0 .

[0111] Step 5: Combine the contact areas A and A determined in the experiment 0 , and the hardness H of the material are substituted into the Suresh model formula to calculate the residual thermal stress of the porcelain bushing.

[0112] In step 3, when the nanoindentation test is carried out on the sample, the indenter randomly selects an area on the loading surface of the sample and performs multiple indentations using the dot matrix method to form an indentation point array, and collects the load-displacement curve of the indenter at each indentation; the indenter is a diamond Berkovich indenter; the row spacing and column spacing of the indentation point array are both 300 μm, and the indentation load of the indenter is 10 mN; the contact point in the load-displacement curve is determined, that is, the point where the load suddenly increases, marking the first time the indenter contacts the sample surface; in the elastic region of the curve, that is, the linear part of the curve, the contact area A and the maximum load P are extracted. max The contact area A 0 ; The indentation matrix layout is 4×4, and the indentation load is 10mN.

[0113] In step 4, calculate the contact area A. For the Berkovich indenter, use the formula to calculate;

[0114] Where: h is the penetration depth of the indenter, S is the contact stiffness, is the elastic modulus of the indenter, P is the load applied by the indenter;

[0115] In step 5, the Suresh model calculates the residual thermal stress The formula is:

[0116] .

[0117] Among them, H can be predetermined by experimental data and material properties.

[0118] For example, the hardness H can be calculated by the following formula:

[0119] ;

[0120] Substituting the expression for contact area A into the equation, we obtain:

[0121] ;

[0122] Step 6: Analyze the stress distribution inside the porcelain bushing by comparing the residual thermal stress in different areas.

[0123] The mean value and standard deviation of residual thermal stress of all pressing points are calculated; the residual thermal stress value is standardized, and the stress concentration area is determined based on the standardized residual thermal stress value. The stress concentration area includes a high stress concentration area, a medium stress concentration area and a low stress concentration area: the area with a standardized residual thermal stress value greater than a first threshold is defined as a high stress concentration area; the area with a standardized residual thermal stress value not greater than the first threshold but greater than the second threshold is defined as a medium stress concentration area; the area with a standardized residual thermal stress value not greater than the second threshold but greater than the third threshold is defined as a low stress concentration area.

[0124] The calculation formula for the mean residual thermal stress is:

[0125] ;

[0126] Where: is the mean value of residual thermal stress, N is the total number of press-in points, i is the press-in point number, , is the residual thermal stress value of the i-th pressing point;

[0127] The calculation formula of the standard deviation of residual thermal stress is:

[0128] ;

[0129] Where: is the standard deviation of residual thermal stress;

[0130] The standard deviation of residual thermal stress is a statistic used to measure the degree of dispersion of a set of residual thermal stress values ​​relative to their mean. If the standard deviation is small, it means that the residual thermal stress values ​​of all measuring points are relatively close to the mean, indicating that the stress distribution of the material in this area is relatively uniform; if the standard deviation is large, it means that the residual thermal stress values ​​of the measuring points are quite different, indicating that the stress state of the material may be uneven, which may lead to unstable performance of the material in practical applications.

[0131] By taking the value of the standard deviation, the distribution of internal stress in the porcelain bushing can be effectively evaluated. If the standard deviation is large, it may indicate that there is potential stress concentration in certain areas of the pipeline, which may lead to fatigue or rupture of the material.

[0132] The residual thermal stress value of each pressing point is standardized to obtain the standardized residual thermal stress value, and the calculation formula is:

[0133] ;

[0134] Where: is the normalized residual thermal stress value.

[0135] The standardized residual thermal stress value is the result of converting the residual thermal stress value of each indentation point relative to the overall mean and standard deviation, which describes the deviation of the residual thermal stress value of each indentation point relative to the mean; the standardized value has a unified dimension, which allows the residual thermal stress values ​​of different measurement points to be compared under the same standard, making it easy to identify those values ​​far from the average level, that is, extreme values ​​or outliers; a positive standardized residual thermal stress value indicates that the residual thermal stress of the point is higher than the mean, and a negative standardized residual thermal stress value indicates that it is lower than the mean; a larger absolute value indicates that the deviation of the residual thermal stress of the point from the mean is more significant.

[0136] The high stress concentration area is a set of indentation points whose normalized residual thermal stress values ​​are greater than the first threshold, the medium stress concentration area is a set of indentation points whose normalized residual thermal stress values ​​are not greater than the first threshold but greater than the second threshold, and the low stress concentration area is a set of indentation points whose normalized residual thermal stress values ​​are not greater than the second threshold but greater than the third threshold.

[0137] Normalized residual thermal stress values ​​can help identify data points that deviate greatly from the mean, making it easier to find potential defects or stress concentration areas. Normalized values ​​can be displayed more clearly on the chart to more intuitively observe the stress distribution. For example, a histogram or thermogram of normalized residual thermal stress values ​​can clearly show stress concentration areas.

[0138] By calculating the mean and standard deviation of the residual thermal stress of all the pressing points, a quantitative analysis of the stress distribution is provided, which can effectively judge the uniformity and discreteness of the internal stress of the porcelain bushing. The process of standardizing the residual thermal stress value eliminates the numerical difference between different pressing points, making the division of the stress concentration area more objective and reasonable. By setting specific thresholds, it is divided into high, medium and low stress concentration areas, which makes it easy to quickly locate potential weaknesses or defects and realize a comprehensive evaluation of the internal stress distribution of the material.

[0139] Step 7: Evaluate the damage mode of the porcelain bushing based on the distribution and magnitude of the residual thermal stress.

[0140] Obtain stress area proportion data, the stress area proportion data includes the proportion of high stress area, the proportion of medium stress area and the proportion of low stress area; obtain stress area residual thermal stress standard deviation data, the stress area residual thermal stress standard deviation data includes the residual thermal stress standard deviation of high stress concentration area, the residual thermal stress standard deviation of medium stress concentration area and the residual thermal stress standard deviation of low stress concentration area; obtain a damage mode stress condition set stored in the database, the damage mode stress condition set includes several damage mode stress condition data, the damage mode stress condition data includes stress area proportion parameter data, high stress concentration area residual thermal stress parameter standard deviation, medium stress concentration area residual thermal stress parameter standard deviation and low stress concentration area residual thermal stress parameter standard deviation, stress area proportion parameter data includes high stress area proportion parameter value, medium stress area proportion parameter value and low stress area proportion parameter value;

[0141] The stress area proportion data and the residual thermal stress standard deviation data of the stress area are combined and recorded as the actual situation data of the stress area; the actual situation data of the stress area are compared with the stress situation data of the damage mode one by one to obtain the stress situation comparison value; the damage mode corresponding to the smallest stress situation comparison value stored in the database is recorded as the damage mode of the high-voltage porcelain bushing that has been exploded and damaged.

[0142] Each damage mode stress condition data corresponds to a damage mode in the database. The proportion of high stress areas is the ratio of the total number of press-in points whose standardized residual thermal stress values ​​are greater than the first threshold to the number of all press-in points. The proportion of medium stress areas is the ratio of the total number of press-in points whose standardized residual thermal stress values ​​are not greater than the first threshold but greater than the second threshold to the number of all press-in points. The proportion of low stress areas is the ratio of the total number of press-in points whose standardized residual thermal stress values ​​are not greater than the second threshold but greater than the third threshold to the number of all press-in points.

[0143] By quantifying the proportion of stress areas and the standard deviation of residual thermal stress, the unevenness of stress distribution on the sample can be specifically evaluated, thereby more accurately identifying high-risk areas on the sample, thereby helping to determine the damage mode of the sample. By systematically storing the stress conditions of the damage mode, it is easy to call and compare later, and possible explosion damage modes can be identified.

[0144] The calculation formula of stress condition comparison value is as follows:

[0145] ;

[0146] Where: is the stress comparison value obtained by comparing the actual data of the stress area with the stress data of the ath damage mode. is the stress area comparison coefficient of the stress condition data of the ath damage mode, is the stress area standard deviation comparison coefficient of the stress condition data of the ath damage mode, Stored in the database The weight factor of Stored in the database The weight factor of , a is the number of the damage mode stress condition data;

[0147] The stress condition comparison value represents the degree of match between the actual stress area condition and the specific damage mode. The lower the comparison value, the higher the similarity between the actual situation and the damage mode.

[0148] By considering two different coefficients (stress area comparison coefficient and standard deviation comparison coefficient), the formula can fully reflect the stress distribution, that is, it takes into account the amount of stress and also pays attention to the discreteness of its distribution, thereby providing a more refined analysis, helping to more accurately identify potential damage modes and promote timely response and maintenance. It can be adjusted and applied to different types of materials and structures, has a certain degree of versatility, and is suitable for stress analysis and damage pattern identification in a variety of engineering scenarios.

[0149] The calculation formula of stress area comparison coefficient is as follows:

[0150] ;

[0151] Where: is the proportion of high stress area, is the proportion of the medium stress area, is the proportion of low stress area, is the parameter value of the proportion of high stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the medium stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the low stress area in the stress condition data of the ath damage mode;

[0152] formula The design provides a clear comparison basis for the stress distribution of different damage modes by quantifying the relative proportion differences of high, medium and low stress areas, comprehensively considering various stress areas to ensure that no single factor is biased, thereby improving the accuracy and reliability of the analysis results.

[0153] The calculation formula of stress area standard deviation comparison coefficient is as follows:

[0154] ;

[0155] Where: is the standard deviation of residual thermal stress in high stress concentration area, is the standard deviation of residual thermal stress in the stress concentration area, is the standard deviation of residual thermal stress in the low stress concentration area, is the standard deviation of residual thermal stress parameters in the high stress concentration area of ​​the stress condition data of the ath damage mode, is the standard deviation of residual thermal stress parameters in the stress concentration area of ​​the a-th damage mode stress condition data, is the standard deviation of the residual thermal stress parameter in the low stress concentration area of ​​the stress condition data of the ath damage mode.

[0156] formula The design provides an in-depth evaluation of damage modes by incorporating the standard deviation of residual thermal stresses in high, medium, and low stress concentration areas into the analysis. This approach of focusing on the amplitude and uncertainty of stress fluctuations makes the evaluation results more sensitive and accurate. The use of natural logarithmic functions effectively reduces the impact of a large range of data and highlights the importance of relative changes, thereby simplifying the comparison of complex data. Comprehensive consideration of the standard deviations of various stress areas enables this formula to provide feedback on damage modes from multiple dimensions, providing a comprehensive basis for fault diagnosis and risk assessment.

[0157] This embodiment is specifically described by the following description:

[0158] The standard material is set as aluminum block, and the standard material test data of the nanoindentation tester is is 2.8%, is 1.87%, 0.49%, is 4.9%, 3%, 2%, 0.5%, 5%, is 0.3, is 0.2, is 0.2, is 0.3, Bp is calculated to be 0.96, and the test deviation matching value threshold is 1. Since Bp is less than the test deviation matching value threshold, the error of the nanoindentation tester is within the normal error range.

[0159] A sample with a diameter of 40 mm and a height of 8 mm was cut from a damaged high-voltage porcelain bushing. The sample surface was carefully ground and polished to ensure that its roughness reached the nanometer level (less than 10 nanometers) to meet the test requirements. The upper and lower end surfaces of the sample were machined to be parallel to each other to ensure that the load can be evenly distributed during the indentation process.

[0160] Detection environment data and allowable deviation matching data 280lx, 6Hz, 300lx, is 5Hz, the comparison coefficient is 0.74, and the comparison results are 0.1μm, For 5GU.

[0161] Sample surface data 0.25μm, is 48GU, 0.3μm, For 50GU, 0.1μm, The surface treatment comparison threshold is 1.1. Since Bm is less than the surface treatment comparison threshold, the surface treatment of the sample to be tested is qualified and is marked as a test sample that can be tested by nanoindentation test.

[0162] Nanoindenter using a diamond Berkovich indenter. The elastic modulus E of the diamond Berkovich indenter tip =1140GPa=1140×10 9 Pa, multiple indentations were performed on the loading surface of the sample using a dot matrix method to form a 4 × 4 indentation point array, a load of 10 mN was applied to each point, the maximum indentation depth was 500 nm, and a series of load-displacement data were collected.

[0163] ;

[0164] Where P is the load applied by the indenter (N), h is the penetration depth of the indenter (m), S is the contact stiffness (N / nm), and E tip is the elastic modulus of the indenter (Pa). S=0.012N / nm, the specific data is shown in Table 1:

[0165] Table 1 Load-displacement data examples

[0166]

[0167] The contact areas of the 16 points were calculated according to the formula, and the average contact area was calculated to be 279.3nm 2 According to step 4, the hardness H can be calculated by the following formula:

[0168] ;

[0169] Using the average hardness of the material determined experimentally beforehand, which is 1.79 GPa, the contact area without load is 300 nm²: The residual thermal stresses were calculated using the Suresh model .

[0170] ;

[0171] The average value of residual thermal stress is 1.83×10 7 Pa. By comparing the residual thermal stress in different areas, it is found that the residual thermal stress distribution inside the porcelain bushing is relatively uniform, but there is a slight stress concentration in some areas. In order to verify the accuracy and reliability of the method of this embodiment, the calculated residual thermal stress is compared with the results of other residual stress detection methods, such as X-ray diffraction. The comparison results show that the residual thermal stress data obtained by this method is basically consistent with the results of other methods, thus proving the effectiveness of this method.

Claims

1. A method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology, characterized in that: The method comprises the following steps: Step 1, perform a performance test on the nanoindentation tester to determine that its error is within a normal error range; Step 2: When the error of the nanoindentation tester is within the normal error range, the damaged high-voltage porcelain bushing is cut into a plurality of samples to be screened suitable for nanoindentation testing, and the sample surface data of each sample is obtained after the samples to be screened are polished, and the test samples suitable for nanoindentation testing are screened based on the sample surface data, wherein the sample surface data includes surface roughness, surface glossiness, number of surface cracks, and number of surface stains; Step 3, using a nanoindenter within a normal error range to perform an indentation experiment on the test sample, and recording the load-displacement curve of the indenter; Step 4: Analyze the load-displacement curve and calculate the contact area A and the maximum load P. max The contact area A0 at this time; Step 5: Combine the contact area A and A0 determined in the experiment, and the hardness H of the material, and substitute them into the Suresh model formula to calculate the residual thermal stress of the porcelain bushing; Step 6: Analyze the stress distribution inside the porcelain bushing by comparing the residual thermal stress in different areas; Step 7: Evaluate the damage mode of the porcelain bushing according to the distribution and magnitude of the residual thermal stress; In step 3, when the nanoindentation test is performed on the sample, the indenter randomly selects an area on the loading surface of the sample and performs multiple indentations using a dot matrix method to form an indentation point array, and collects the load-displacement curve of the indenter during each indentation; The indenter is a diamond Berkovich indenter; The row and column spacing of the indentation point array is 300 μm, and the indentation load of the indenter is 10 mN; Determine the contact point in the load-displacement curve, that is, the point where the load suddenly increases, marking the first time the indenter contacts the sample surface; in step 3, extract the contact area A and the maximum load P in the elastic region of the curve, that is, the part of the curve that is linear. max The contact area A0 at this time; In step 4, calculate the contact area A. For the Berkovich indenter, use the formula to calculate; Where: h is the penetration depth of the indenter, S is the contact stiffness, is the elastic modulus of the indenter, P is the load applied by the indenter; In step 5, the Suresh model calculates the residual thermal stress The formula is: ; In step 6, analyzing the stress distribution inside the porcelain bushing includes the following steps: Calculate the mean value and standard deviation of residual thermal stress of all pressing points; The residual thermal stress value is normalized, and the stress concentration area is determined based on the normalized residual thermal stress value. The stress concentration area includes a high stress concentration area, a medium stress concentration area, and a low stress concentration area: The area where the normalized residual thermal stress value is greater than the first threshold value is defined as a high stress concentration area; A region where the normalized residual thermal stress value is not greater than the first threshold value but greater than the second threshold value is defined as a medium stress concentration region; A region where the normalized residual thermal stress value is not greater than the second threshold value but greater than the third threshold value is defined as a low stress concentration region; In step 7, the damage mode of the porcelain bushing is evaluated according to the distribution and size of the residual thermal stress, which specifically includes the following steps: Obtaining stress area proportion data, the stress area proportion data including high stress area proportion, medium stress area proportion and low stress area proportion; Obtaining the standard deviation data of residual thermal stress in the stress area, the standard deviation data of residual thermal stress in the stress area includes the standard deviation of residual thermal stress in the high stress concentration area, the standard deviation of residual thermal stress in the medium stress concentration area and the standard deviation of residual thermal stress in the low stress concentration area; A damage mode stress condition set stored in a database is obtained, the damage mode stress condition set includes a number of damage mode stress condition data, the damage mode stress condition data includes stress area proportion parameter data, high stress concentration area residual thermal stress parameter standard deviation, medium stress concentration area residual thermal stress parameter standard deviation and low stress concentration area residual thermal stress parameter standard deviation, stress area proportion parameter data includes high stress area proportion parameter value, medium stress area proportion parameter value and low stress area proportion parameter value; The stress area proportion data and the residual thermal stress standard deviation data of the stress area are combined and recorded as the actual situation data of the stress area; Compare the actual situation data of the stress area with the stress situation data of the damage mode one by one to obtain the stress situation comparison value; The damage mode corresponding to the minimum stress comparison value stored in the database is recorded as the damage mode of the high-voltage porcelain bushing that has been damaged by explosion; The calculation formula of stress condition comparison value is as follows: ; Where: is the stress condition comparison value obtained by comparing the actual data of the stress area with the stress condition data of the ath damage mode, is the stress area comparison coefficient of the stress condition data of the ath damage mode, is the stress area standard deviation comparison coefficient of the stress condition data of the ath damage mode, Stored in the database The weight factor of Stored in the database The weight factor of , a is the number of the damage mode stress condition data; The calculation formula of stress area comparison coefficient is as follows: ; Where: is the proportion of high stress area, is the proportion of the medium stress area, is the proportion of low stress area, is the parameter value of the proportion of high stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the medium stress area in the stress condition data of the ath damage mode, is the parameter value of the proportion of the low stress area in the stress condition data of the ath damage mode; The calculation formula of stress area standard deviation comparison coefficient is as follows: ; Where: is the standard deviation of residual thermal stress in high stress concentration area, is the standard deviation of residual thermal stress in the stress concentration area, is the standard deviation of residual thermal stress in the low stress concentration area, is the standard deviation of residual thermal stress parameters in the high stress concentration area of ​​the stress condition data of the ath damage mode, is the standard deviation of residual thermal stress parameters in the stress concentration area of ​​the a-th damage mode stress condition data, is the standard deviation of the residual thermal stress parameter in the low stress concentration area of ​​the stress condition data of the ath damage mode.

2. According to claim 1, a method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology is characterized in that: In step 1, a performance test is performed on the nanoindentation tester to determine that its error is within a normal error range, including the following steps: Use a nanoindentation tester to perform an indentation experiment on a standard material to obtain standard material test data, which includes test indentation recovery rate, test unloading curve slope, test depth drift rate, and test elastic modulus; Obtain actual data of standard materials, including actual indentation recovery rate, actual unloading curve slope, actual depth drift rate, and actual elastic modulus; The standard material test data and the standard material actual data are processed to obtain the standard material test deviation data, which includes the indentation recovery rate deviation, the unloading curve slope deviation, the depth drift rate deviation, and the elastic modulus deviation; Based on the standard material test deviation data and the material test deviation allowable data stored in the database, the test deviation matching value is obtained. The material test deviation allowable data includes the indentation recovery rate allowable deviation, the unloading curve slope allowable deviation, the depth drift rate allowable deviation and the elastic modulus allowable deviation; The test deviation matching value is compared with the test deviation matching value threshold stored in the database. If the test deviation matching value is less than the test deviation matching value threshold, the error of the nanoindentation tester is within the normal error range. If the test deviation matching value is not less than the test deviation matching value threshold, the error of the nanoindentation tester is outside the normal error range, and the standard material test deviation data is compared with the standard material test deviation matching data stored in the database to determine the closest standard material test deviation matching data; Based on the closest standard material test deviation matching data, the nanoindentation tester failure cause corresponding to the closest standard material test deviation matching data stored in the database is obtained.

3. According to claim 2, a method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology is characterized in that: The method of determining the closest standard material test deviation matching data comprises the following steps: Comprehensively analyze the standard material test deviation data and the standard material test deviation matching data stored in the database to obtain the test comparison value. The standard material test deviation matching data includes the indentation recovery rate matching deviation, the unloading curve slope matching deviation, the depth drift rate matching deviation, and the elastic modulus matching deviation; The standard material test deviation matching data stored in the database corresponding to the largest test comparison value is the closest standard material test deviation matching data.

4. According to claim 1, a method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology is characterized in that: In the step 2, the damaged high-voltage porcelain bushing is cut into samples with a diameter less than Φ50 mm and a height less than 10 mm, and the sample surface is ground and polished to ensure that the roughness of the loading surface reaches the nanometer level and is less than 1 / 5 of the average indentation depth; the upper and lower end surfaces of the sample are parallel to each other to ensure uniform distribution of the load during the indentation process.

5. According to claim 1, a method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology is characterized in that: In step 2, screening a test sample suitable for nanoindentation testing based on sample surface data includes the following steps: Determine whether the number of surface cracks or surface stains is not zero. If any of them is not zero, the surface treatment is unqualified and the sample is marked as unsuitable for nanoindentation testing. If both are zero, the sample surface definition data is obtained, and the sample surface definition data includes surface definition roughness and surface definition glossiness; Acquire the sample surface allowable deviation data, the sample surface allowable deviation data includes the roughness allowable deviation value and the gloss allowable deviation value; Comprehensively analyze the sample surface data, sample surface definition data and sample surface allowable deviation data to obtain the surface treatment comparison value; The surface treatment comparison value is compared with the surface treatment comparison threshold stored in the database. If the surface treatment comparison value is less than or equal to the surface treatment comparison threshold, the surface treatment of the sample to be tested is qualified and is marked as a test sample capable of nanoindentation testing. If the surface treatment comparison value is greater than the surface treatment comparison threshold, the size of the sample to be tested is unqualified and cannot be subjected to nanoindentation testing. In this case, the sample is replaced and polished again.

6. The method for detecting thermal stress of high-voltage porcelain bushing based on nanoindentation technology according to claim 5 is characterized in that: The method of obtaining the sample surface allowable deviation data comprises the following steps: Acquire an allowable deviation data matching set stored in a database, the allowable deviation data matching set including allowable deviation matching data, and the allowable deviation matching data including an environment comparison brightness and an indoor dust content comparison value; Obtaining the detection environment data when collecting the sample surface data of the sample to be screened, the detection environment data includes the environment brightness and indoor dust content; Compare the detection environment data with the allowable deviation matching data to obtain the comparison coefficient; The allowable deviation matching data corresponding to the largest comparison coefficient corresponds to the sample surface allowable deviation data stored in the database, which is the sample surface allowable deviation data corresponding to the detection environment data.

Citation Information

Patent Citations

  • Method for measuring residual stress on surface of material by using nanoindentation technology

    CN113188890A